The effect of forest fragmentation about the accumulation of litter in Deciduous Forest - Alves, Marcelo Plada; Viera, Márcio; Schumacher, Mauro Valdir (Revista Ecologia e Nutrição Florestal - ENFLO, 2015)
The objective of this study was to evaluate the effect of forest fragmentation on the accumulation of litter in Deciduous Forest in Silveira Martins, RS. Fifteen sampling points were established along the fragment, marked with the aid of Google Earth program and covered with the use of GPS during data collection, and measure tape to identify the distance established point-to-point: eight points were marked in the north-south direction; points in the east-west; and the central point equidistant 25m each of them. For each point, five samples of litter accumulated were collected using wooden frame with size 0.25 m x 0.25 m, after collecting them, the material was stored in paper-bags. In the laboratory, the samples were separated into the following fractions: leaves, twigs (diameter ≤1.0 cm) and miscellaneous (other waste), putting them to drying at a temperature of 70°C, and weighted on a precision scale (0, 01g). There were variations in the litter disposition from from east to south directions in relation to other averageof deposition, confirming that this fragmentation influenced in the accumulation of the litter, because there was not found less concentration in streme points and more in the central points of the forest fragmentation. In the Chemical analisis, higher concentration of N (20.42 g kg-1) and Ca (13.82 g kg-1) were verified, however in relation to macronutrients, there was a large concentration of Mn (815.29 g kg-1).